Osteocalcin modulates parathyroid cell function in human parathyroid tumors - Verdelli, Chiara; Tavanti, Giulia Stefania; Forno, Irene; Vaira, Valentina; Maggiore, Riccardo; Vicentini, Leonardo; Dalino Ciaramella, Paolo; Perticone, Francesca; Lombardi, Giovanni; Corbetta, Sabrina (Frontiers in Endocrinology, 2023)
The bone matrix protein osteocalcin (OC), secreted by osteoblasts, displays endocrine effects. We tested the hypothesis that OC modulates parathyroid tumor cell function. Primary cell cultures derived from parathyroid adenomas (PAds) and HEK293 cells transiently transfected with the putative OC receptor GPRC6A or the calcium sensing receptor (CASR) were used as experimental models to investigate gamma-carboxylated OC (GlaOC) or uncarboxylated OC (GluOC) modulation of intracellular signaling. In primary cell cultures derived from PAds, incubation with GlaOC or GluOC modulated intracellular signaling, inhibiting pERK/ERK and increasing active beta-catenin levels. GlaOC increased the expression of PTH, CCND1 and CASR, and reduced CDKN1B/p27 and TP73. GluOC stimulated transcription of PTH, and inhibited MEN1 expression. Moreover, GlaOC and GluOC reduced staurosporin-induced caspase 3/7 activity. The putative OC receptor GPRC6A was detected in normal and tumor parathyroids at membrane or cytoplasmic level in cells scattered throughout the parenchyma. In PAds, the membrane expression levels of GPRC6A and its closest homolog CASR positively correlated; GPRC6A protein levels positively correlated with circulating ionized and total calcium, and PTH levels of the patients harboring the analyzed PAds. Using HEK293A transiently transfected with either GPRC6A or CASR, and PAds-derived cells silenced for CASR, we showed that GlaOC and GluOC modulated pERK/ERK and active beta-catenin mainly through CASR activation. In conclusion, parathyroid gland emerges as a novel target of the bone secreted hormone osteocalcin, which may modulate tumor parathyroid CASR sensitivity and parathyroid cell apoptosis